2019
DOI: 10.2528/pierc19060602
|View full text |Cite
|
Sign up to set email alerts
|

Low Profile, High Gain and Wideband Circularly Polarized Antennas Using Hexagonal Shape Parasitic Patches

Abstract: This paper proposes low profile, high gain and wideband circularly polarized (CP) microstrip antennas (MSA), using gap coupled parasitic patches (PPs) on superstrate layer. Printed and suspended probe fed, CP MSAs are designed on a 1.59 mm thick FR4 substrate, and an array of closely spaced hexagonal PPs are printed on the bottom side of the 1.59 mm thick FR4 superstrate and placed at a height about λ 0 /8 above the ground plane, where λ 0 is the free space wavelength, corresponding to the central frequency of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…[19], switching from low-permittivity substrates to high-permittivity substrates [20], and adding Gap-coupled parasitic components are the most widely used methods for increasing bandwidth and antenna gain. The literature on gap-coupled electromagnetically coupled patch (EMCP) antennas for wireless applications is extensive [24][25]. Varshney et al showed a fan-shaped tri-arm circular monopole antenna that loads its parasitically split ring resonator (SRR) triplet in the ground section to improve bandwidth [26].…”
Section: Introductionmentioning
confidence: 99%
“…[19], switching from low-permittivity substrates to high-permittivity substrates [20], and adding Gap-coupled parasitic components are the most widely used methods for increasing bandwidth and antenna gain. The literature on gap-coupled electromagnetically coupled patch (EMCP) antennas for wireless applications is extensive [24][25]. Varshney et al showed a fan-shaped tri-arm circular monopole antenna that loads its parasitically split ring resonator (SRR) triplet in the ground section to improve bandwidth [26].…”
Section: Introductionmentioning
confidence: 99%
“…One of the most extensively used methods for enhancing the bandwidth and gain of microstrip patch antennas is to use gap coupled parasitic components. There have been many papers published in the literature on electromagnetically fed gap coupled patch antennas for wireless applications [10][11]. In [12] a triple band proximity fed 2x1 array antenna with defected ground plane is presented.…”
Section: Introductionmentioning
confidence: 99%
“…Since the multiple patches are used for catering to the different frequency bands, the antenna size is large here. For the gain enhancement in triple band MSA, artificial magnetic conductors are used in Ghosh et al, 16 while a metamaterial is used in broadband DP MSA as reported in Wang et al 17 The use of superstrate with multiple parasitic patches increases the fabrication complexity in the high gain wideband circular polarized (CP) antenna 18 . A wideband differentially fed stacked patch antenna is reported for the 1,660–2,660 MHz frequency range 19 .…”
Section: Introductionmentioning
confidence: 99%
“…circular polarized (CP) antenna. 18 A wideband differentially fed stacked patch antenna is reported for the 1,660-2,660 MHz frequency range. 19 Though fabricated on thicker substrate (0.07λ 0 ), the MSA BW is small.…”
mentioning
confidence: 99%